2020
DOI: 10.1007/s00066-020-01599-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of pulmonary toxicities in the combination of whole lung irradiation and high-dose chemotherapy for Ewing sarcoma patients with lung metastases: a review

Abstract: Background Whole lung irradiation (WLI) represents an important part of multimodal therapy in Ewing sarcoma (EwS) patients diagnosed with pulmonary metastases. This review discusses pulmonary toxicity in EwS patients with pulmonary metastases treated with WLI, who received different modes of high-dose chemotheray (HD-Cth). Methods Literature was compiled using the Cochrane Library, PubMed database, and the National Institute of Health (NIH) clinical trials register. Relevant patient information, including natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Only a minority of patients showed significant pulmonary function abnormality after WLI [ 189 ]. The risk of adverse lung effects after WLI depends on several factors, including cumulative radiation dose and dose per fraction, high-dose chemotherapeutic regimen, and time interval between high-dose treatment and WLI [ 193 ]. The radiosensitization effect and toxicity of busulfan-containing chemotherapy before RT for EwS has been repeatedly described [ 192 , 194 ].…”
Section: Local Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Only a minority of patients showed significant pulmonary function abnormality after WLI [ 189 ]. The risk of adverse lung effects after WLI depends on several factors, including cumulative radiation dose and dose per fraction, high-dose chemotherapeutic regimen, and time interval between high-dose treatment and WLI [ 193 ]. The radiosensitization effect and toxicity of busulfan-containing chemotherapy before RT for EwS has been repeatedly described [ 192 , 194 ].…”
Section: Local Therapymentioning
confidence: 99%
“…The radiosensitization effect and toxicity of busulfan-containing chemotherapy before RT for EwS has been repeatedly described [ 192 , 194 ]. Severe toxicities leading to death have been observed in single patients who received high-dose large-volume RT following busulfan-containing high-dose treatment [ 193 , 194 , 195 ]. In patients with an indication for RT, the patient will not be offered busulfan-containing high-dose treatment if there are critical organs such as gut or lung in the fields, unless the technique can be provided which limits the dose to critical organs.…”
Section: Local Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Few published data to evaluate the feasibility of WLI combined with high-dose chemotherapy are available, due to the relatively limited number of cohorts and the lack of treatment homogeneity across the studies [ 34 ]. This study is the largest report on toxicity and outcome following BU-MEL and WLI in lung metastatic ES.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum time interval of eight weeks between BU-MEL and WLI may have contributed to limit the incidence and the grade of the observed toxicities. In a recent review, a time interval of 30–60 days between HDCT and WLI showed a significant impact on pulmonary function disorders [ 34 ].…”
Section: Discussionmentioning
confidence: 99%